2023
DOI: 10.3390/ijerph20032281
|View full text |Cite
|
Sign up to set email alerts
|

Understanding for Prevention: Qualitative and Quantitative Analyses of Suicide Notes and Forensic Reports

Abstract: Suicide risk is associated with vulnerabilities and specific life events. The study’s objective was to explore the relevance of data from forensic documentation on suicide deaths to the design of person-centered preventive strategies. Descriptive and thematic analyses were conducted of forensic observations of 286 deaths by suicide, including some with suicide notes. Key findings included the influence of health-and family-related adverse events, emotional states of loss and sadness, and failures of the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
3
0
1
Order By: Relevance
“…Suicide notes written by Indonesians and in the Indonesian language have also not been widely researched. This is evidenced by previous studies (Fata et al, 2021;Maharani et al, 2022;Malini & Tan, 2016;Masood, 2021;Mejías-Martín et al, 2023) that addressed English suicide notes. Therefore, the current research is expected to be able to contribute to the horizon of forensic linguistics from the findings of Indonesian suicide notes.…”
Section: Introductionmentioning
confidence: 58%
“…Suicide notes written by Indonesians and in the Indonesian language have also not been widely researched. This is evidenced by previous studies (Fata et al, 2021;Maharani et al, 2022;Malini & Tan, 2016;Masood, 2021;Mejías-Martín et al, 2023) that addressed English suicide notes. Therefore, the current research is expected to be able to contribute to the horizon of forensic linguistics from the findings of Indonesian suicide notes.…”
Section: Introductionmentioning
confidence: 58%
“…Finally, the non-publication of suicide notes was 96% in our study. However, the news reports did not clarify whether the victims had left any notes or whether they were collected as clues or evidence within the investigation process at the scene, which could have artificially influenced compliance with this criterion 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente, la no publicación de notas suicidas fue de 96% en nuestro estudio. Sin embargo, las noticias analizadas no aclararon si las víctimas habían dejado alguna nota o si fueron recogidas como indicios o evidencias dentro del proceso de investigación en el lugar de los hechos, lo que podría haber influido artificialmente en el cumplimiento de este criterio (35) .…”
Section: Discussionunclassified
“…In the study conducted by Loret et al (1999) that investigated the notes found in 183 cases of suicide occurring in three districts of the province of Alicante, in Spain, the content analysis retained the categories: Farewell, instructions, apology and accusation. Mejías-Martín et al (2023) conducted a study based on 286 forensic observations in Spain, which included suicide notes. That study revealed the impact of adverse health and family-related events, emotional states of grief and sadness, and failures within the healthcare system in recognizing and responding to signs of vulnerability.…”
mentioning
confidence: 99%